Documenting Communications and Communicating Documents: Developing Thesis Online Supervising in Distance Education - Djoko Rahardjo (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2021)
Supervising master's program theses frequently present difficulties, particularly in higher distance education, where the majority of students live in completely separate locations from their mentors. This condition requires a great deal of time, energy, and money. Additionally, the institution made it difficult to control the process. This study makes a recommendation for resolving this supervising dilemma. To accomplish these goals, an exploratory study is conducted through the design of a learning management system that will be used to supervise processes. The design establishes a synchronous and asynchronous communication system between students and mentors. The outcome is a description of the thesis supervising process's requirements and the thesis supervising model developed in Moodle.